Construção e caracterização de micro-células voltamétricas para análises em volumes reduzidos - Silva, Rodrigo Amorim Bezerra da (2009)
In this work the construction and characterization of alternative voltammetric microcells for the analysis of small volumes are presented. Two electrode arrangements are proposed. In the first arrangement three electrodes were incorporated into micropipette tips and, in the second one, the three electrodes were inserted at the interior of microchannels (thin layer cells). For their constructions, it was used cheap and/or reusable (disposable) materials such as polycarbonate basis (from CD-Rs), micropipette tips, silver and graphite composites, metallic wires, etc. According to this view, it was developed a graphite composite containing epoxy adhesive in the presence of cyclohexanone solvent. This composite, after the optimization of the proportions of its constituent parts, can be used as material for electrodes, such as pseudo-reference, auxiliary and working electrodes and for electrical contact. Cyclic voltammograms obtained in solution of potassium ferrocyanide has showed that electrodes constructed with this material have high durability, good interelectrode reproducibility (relative standard deviation = 4%; n=5), stability in a microcell where the three electrodes are situated in a micropipette tip (RSD = 1.82 %; n=10) and when the electrodes are inserted in a thin layer cell (RSD = 1%; n = 8; Cd e Pb). Good correlation coefficients were obtained for amperograms of increasing concentrations of potassium ferrocyanide in basic medium (R = 0.999), and voltammograms for increasing concentrations of Pb and Cd in acid medium, as much for the microcell constructed in micropipette tip (R=0,998 and 0,997) as for the thin layer microcell (R = 0.996 and 0.996). Studies proved that similar relative standard deviations are obtained (repeatibility and reproducibility) in case of experiments carried out using composite materials as pseudo-reference and auxiliary electrodes are compared to those obtained using commercial reference (Ag/AgCl/KCl sat.) and auxiliary (platinum) electrodes. These results are independent of pH and electrolyte. A better performance was observed for microcells constructed on micropipette tips containing gold as working electrode (in micrometric scale) if the gold wire was previously immersed in a PVC solution and after immobilized in the interior of the micropipette tip (using epoxy adhesive). When the graphite composite was used as working electrode, a sensitive improvement was obtained by their performance when the internal surface of the micropipette tip was previously covered with epoxy adhesive and the composite introduced subsequently. It is supposed that in both cases, this ability inhibited or delayed water infiltration. Similar cyclic voltammetric responses were obtained for comparative studies between small volumes (up to 3 mL) and large volumes (~ 5 mL), used in conventional electrochemical cells, on the micropipette tip arrangement. The microcells developed in this work are practical because it is not necessary a specific support for the positioning of the three electrodes in a cell as it occurs with commercial approaches. Moreover, using the same electrodes arrangements is possible to work in different experimental conditions (stationary and flow rate mode).